2017
DOI: 10.1589/jpts.29.1993
|View full text |Cite
|
Sign up to set email alerts
|

The effects of calcaneal posture on thoracolumbar alignment in a standing position

Abstract: [Purpose] Severe calcaneus misalignment is correlated with low back pain, and affects pelvic alignment. However, little has been published with regard to the influence of pronation and supination on trunk alignment. Therefore, the present study aimed to investigate the influence of calcaneal inversion on pelvic and trunk alignment. [Subjects and Methods] A 3-dimensional motion analysis system was used to assess pelvic and trunk alignment in 10 healthy male subjects with unilateral and bilateral calcaneus inver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 11 publications
(18 reference statements)
0
1
1
Order By: Relevance
“…It was highlighted that these changes might increase lumbar pain by increasing lumbar lordosis. [12] In the current study, no significant difference was found between the control group and the group of ballet dancers in terms of anterior and posterior pelvic tilt and lumbar lordosis (p>0.05).…”
Section: Discussioncontrasting
confidence: 61%
“…It was highlighted that these changes might increase lumbar pain by increasing lumbar lordosis. [12] In the current study, no significant difference was found between the control group and the group of ballet dancers in terms of anterior and posterior pelvic tilt and lumbar lordosis (p>0.05).…”
Section: Discussioncontrasting
confidence: 61%
“…According to some clinical observations, foot hyperpronation malalignment of the lower extremity and foot may induce structural and biomechanical deficits in the standing position and gait. Consequently, this situation may affect the sacral angle, pelvic inclination, and lumbar lordosis as a compensatory phenomenon, leading to non-specific chronic low back pain [ 7 , 17 , 18 , 19 , 20 , 34 , 35 ]. This situation may cause musculoskeletal imbalances of the lower limb and the occurrence of injuries, such as CLBP [ 4 , 7 , 10 , 36 , 37 ].…”
Section: Discussionmentioning
confidence: 99%